Unsupervised learning with a physics-based autoencoder for estimating the thickness and mixing ratio of pigments - Shitomi, Ryuta; Tsuji, Mayuka; Fujimura, Yuki; Funatomi, Takuya; Mukaigawa, Yasuhiro; Morimoto, Tetsuro; Oishi, Takeshi; Takamatsu, Jun; Ikeuchi, Katsushi (Journal of the Optical Society of America. A, Optics, image science, and vision, 2023)
Layered surface objects represented by decorated tomb murals and watercolors are in danger of deterioration and damage. To address these dangers, it is necessary to analyze the pigments' thickness and mixing ratio and record the current status. This paper proposes an unsupervised autoencoder model for thickness and mixing ratio estimation. The input of our autoencoder is spectral data of layered surface objects. Our autoencoder is unique, to our knowledge, in that the decoder part uses a physical model, the Kubelka-Munk model. Since we use the Kubelka-Munk model for the decoder, latent variables in the middle layer can be interpretable as the pigment thickness and mixing ratio. We conducted a quantitative evaluation using synthetic data and confirmed that our autoencoder provides a highly accurate estimation. We measured an object with layered surface pigments for qualitative evaluation and confirmed that our method is valid in an actual environment. We also present the superiority of our unsupervised autoencoder over supervised learning.